2010
DOI: 10.4049/jimmunol.0902841
|View full text |Cite
|
Sign up to set email alerts
|

IL-7–Dependent B Lymphocytes Are Essential for the Anti-polysaccharide Response and Protective Immunity toStreptococcuspneumoniae

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 71 publications
5
55
0
Order By: Relevance
“…Since B1b cells are the primary responders to the prototypical TI-2 antigen NP-Ficoll, as well as to B. hermsii (2,4,36,40), we analyzed the B1b cell compartments of TACI Ϫ/Ϫ , BAFFR Ϫ/Ϫ , and BAFF Ϫ/Ϫ mice. We found that TACI-, BAFFR-, and BAFF-deficient mice all possessed a comparable frequency of B1b cells, though BAFFR-and BAFFdeficient mice possessed significantly fewer B1 cells than did wildtype or TACI-deficient mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since B1b cells are the primary responders to the prototypical TI-2 antigen NP-Ficoll, as well as to B. hermsii (2,4,36,40), we analyzed the B1b cell compartments of TACI Ϫ/Ϫ , BAFFR Ϫ/Ϫ , and BAFF Ϫ/Ϫ mice. We found that TACI-, BAFFR-, and BAFF-deficient mice all possessed a comparable frequency of B1b cells, though BAFFR-and BAFFdeficient mice possessed significantly fewer B1 cells than did wildtype or TACI-deficient mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For NP-Ficoll immunization, 50 g of 77-NP-loaded-Ficoll (Biosearch Technologies, Petaluma, CA) dissolved in 100 l Dulbecco's phosphate-buffered saline was used to immunize mice intraperitoneally (36). For pneumococcal immunizations, mice were injected intraperitoneally with 1 ϫ 10 8 encapsulated, heat-killed cells of the WU-2 strain of S. pneumoniae (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its effect on B-cell development in HISmice has not been characterized, administration of human IL-7 might augment B-cell development quantitatively and qualitatively (39)(40)(41). For example, IL-7 was shown to increase B-cell receptor (BCR) diversity in mice (40), and IL-7-dependent murine B cells play an important role in generating a T cell-independent responses to a variety of antigens (42).…”
Section: Discussionmentioning
confidence: 99%
“…5). A possible explanation for the comparable NP-specific IgM responses between wild-type and Cxcl13 Ϫ/Ϫ mice after NP-Ficoll immunization could be the participation of other B cell subsets (45) or B1b cells outside the peritoneal cavity. Indeed, we found that Cxcl13 Ϫ/Ϫ mice had a higher frequency of Mac1-negative NP-specific B cells in the blood, MLNs, and spleen than did wild-type mice (Table 1).…”
Section: Mice Np-ficoll Is a Widely Used Model Antigen For Studying mentioning
confidence: 99%